Fact, myth and legend in Matthew Arnold's Westminister Abbey - Braček, Tadej (ELOPE (Ljubljana), 2007)
The paper deals with the multilayered elegy "Westminster Abbey," which was not given a lot of attention by Matthew Arnold's critics. The poem is dedicated to Arnold's life-long friend Dean Stanley, who was, like Arnold himself, "a child of light." The term refers to their common fight against Philistinism in the English society of the time. As the poem is about a real person, it contains real data, such as excerpts from Stanley's life, described in the form of praise. However, the poem also introduces the old Saxon legend of consecration of the Abbey, namely the consecration by the light, performed by the First Apostle (St Peter) himself. In addition to the legend, Arnold also used some classical Greek allusions to depict the late Dean's character. In one of the allusions, Stanley is associated with Demophon, whose immortality was never achieved due to the fault of another human, and in the second he is transformed into an everlasting oracle of the Abbey using the Trophonius, a builder of Delphi, metaphor. All elements of the poem form a homogenous eulogy, making it worthwhile reading for English scholars and students, and possibly a candidate for the English poetic canon.
Keywords: angleška književnost; angleška poezija; Arnold, Matthew: Westminster Abbey; viktorjanska poezija